The political economy of integration : the experience of Mercosur - Cason, Jeffrey W. (Routledge studies in the modern world economy ;, 2011)
This book assesses South America's most ambitious attempt at economic integration, Mercosur, explaining the main - and inherent - weaknesses of the integration effort, through explicit comparison with the European experience with integration.